2009
DOI: 10.1890/090050
|View full text |Cite
|
Sign up to set email alerts
|

The ecology of dust

Abstract: Wind erosion and associated dust emissions play a fundamental role in many ecological processes and provide important biogeochemical connectivity at scales ranging from individual plants up to the entire globe. Yet, most ecological studies do not explicitly consider dust‐driven processes, perhaps because most relevant research on aeolian (wind‐driven) processes has been presented in a geosciences rather than an ecological context. To bridge this disciplinary gap, we provide a general overview of the ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
216
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(218 citation statements)
references
References 50 publications
1
216
0
1
Order By: Relevance
“…Vegetative cover reduces soil exposure, and thus sites currently dominated by annual plants (e.g., abandoned croplands, heavily disturbed sites) can be rehabilitated by establishment of perennial grasses and shrubs that provide protection even in drought years. Most dryland soils are stable until disturbed (Field et al, 2010), and thus reduced surface disturbance (e.g., livestock grazing, off-road vehicles, agricultural activities, fire) in lower elevation regions, especially during drought years, can be highly effective in reducing dust production.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetative cover reduces soil exposure, and thus sites currently dominated by annual plants (e.g., abandoned croplands, heavily disturbed sites) can be rehabilitated by establishment of perennial grasses and shrubs that provide protection even in drought years. Most dryland soils are stable until disturbed (Field et al, 2010), and thus reduced surface disturbance (e.g., livestock grazing, off-road vehicles, agricultural activities, fire) in lower elevation regions, especially during drought years, can be highly effective in reducing dust production.…”
Section: Discussionmentioning
confidence: 99%
“…Eolian dust, moreover, is implicated in a wide range of environmental processes, including soil formation (McTainsh and Strong, 2007), fertilization of continental environments such as forests and lake systems (McTainsh and Strong, 2007), coral contamination (Shinn et al, 2000), and human health problems (Prospero et al, 2005), among others (see Field et al, 2010 for a review). In addition to being a driver of climate and ecological change, eolian dust that accumulates in different environments such as loess/paleosol sequences (Ding et al, 2002), ice cores (Bory et al, 2003), and marine sediments (Yamazaki and Ioka, 1997;Bailey et al, 2011;Roberts et al, 2011) provides an opportunity to study past climate variations and atmospheric dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the average background level of horizontal sediment flux in the study area is ~0.25 g cm -1 day -1 [Li et al, 2007;Bergametti and Gillette, 2010]. These windblown sediments are produced primarily by saltation, a mechanism of aeolian sediment transport that occurs close to the ground (e.g., <1 m), for particles with diameter in the range of 0.02-0.5 mm [Gillette et al, 1997;Field et al, 2010].…”
Section: Discussionmentioning
confidence: 97%